Intracavitary cardiac metastasis of cervical squamous cell carcinoma with immune thrombocytopenia: a rare case report - Liu, Ning; Lv, Deguan; Schneider, Raydonna Rachel; Yang, Hongyan; Zhang, Mingyan; Liu, Yanan; Sun, Meili (Frontiers in Oncology, 2023)
Cervical cancer is a prevalent gynecological malignancy; however, intracavitary cardiac metastasis of cervical squamous cell carcinoma is exceptionally rare. In addition, the co-occurrence of cervical cancer and right ventricular cancer thrombus with autoimmune diseases is extremely uncommon. Furthermore, the role of immune checkpoint inhibitors in the treatment process of such cases remains controversial. Given the scarcity of reported cases, it is imperative to document and highlight this unique presentation, providing novel insights into diagnosis and management strategies. We present the case of an adult patient diagnosed with cervical cancer and concurrent right ventricular cancer thrombus, accompanied by immune thrombocytopenia (ITP). The patient exhibited resistance to conventional ITP drugs, with suboptimal platelet response. However, upon achieving initial control of the tumor, the patient's platelet counts returned to normal. Notably, the addition of immune checkpoint inhibitors targeting PD-L1 resulted in effective tumor control, accompanied by sustained high platelet levels. Unfortunately, during subsequent anti-tumor therapy, the patient experienced a prolonged platelet rise time, rendering continuous effective anti-tumor therapy and anticoagulant therapy unattainable. This led to a gradual increase in intraventricular thrombosis, ultimately resulting in the patient's demise due to circulatory failure. This rare case sheds light on the potential alleviation of ITP in patients with tumor complications through effective antitumor therapy. The successful control of ITP after tumor management highlights the importance of integrated treatment approaches. Furthermore, the inclusion of immune checkpoint inhibitors demonstrated their potential role in achieving tumor control and maintaining platelet levels. However, the prolonged platelet rise time observed during subsequent therapy underscores the challenges in maintaining both effective anti-tumor therapy and anticoagulant therapy, necessitating careful management strategies. This case report emphasizes the need for a comprehensive evaluation and tailored therapeutic interventions in similar complex scenarios. In summary, this case report offers valuable clinical insights into the management of intracavitary cardiac metastasis of cervical squamous cell carcinoma, the coexistence of immune thrombocytopenia, and the potential implications of immune checkpoint inhibitors in such cases. Understanding these rare occurrences and their clinical impact can contribute to improved diagnostic approaches, therapeutic decision-making, and patient outcomes.